2010
DOI: 10.1007/s00277-010-0982-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of coagulation kinetics using thromboelastometry—methodologic influence of activator and test medium

Abstract: Introduction: Renewed interest has arisen in the use of thromboelastography/thromboelastometry in evaluating coagulation kinetics. The test medium, type of activator and its concentration may influence the interpretation of coagulation kinetics. This study aimed to investigate methodological influences of activator and test medium on thromboelastometric parameters of coagulation kinetics. Methods: Dynamic clot formation was evaluated by thromboelastometry using whole blood (WB), platelet rich plasma or platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The Cochrane database review showed, however, that the level of evidence to justify this enthusiasm for TEG use in trauma remains low . Pathologists have generally been less enthusiastic about TEG testing because of poor reproducibility of TEG results in split‐sample testing, as well as further problems in day‐to‐day, machine‐to‐machine, and operator‐to‐operator variability . Hematologists have been concerned with the questions of what observed abnormalities mean and how one uses observed abnormalities to guide rational therapy …”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane database review showed, however, that the level of evidence to justify this enthusiasm for TEG use in trauma remains low . Pathologists have generally been less enthusiastic about TEG testing because of poor reproducibility of TEG results in split‐sample testing, as well as further problems in day‐to‐day, machine‐to‐machine, and operator‐to‐operator variability . Hematologists have been concerned with the questions of what observed abnormalities mean and how one uses observed abnormalities to guide rational therapy …”
Section: Discussionmentioning
confidence: 99%
“…Standardization of the concentrations and preparations of dilute human recombinant (hR) TF (Innovin) for dogs, cats, and horses would be beneficial. Evidence from 3 human studies (LOE 6, Good‐Fair) shows that different agonist concentrations produce dissimilar results, arguing for standardization of agonist concentrations . A 1:50,000 dilution of hR‐TF has been validated and described in 1 ROTEM and multiple TEG publications in small animals .…”
Section: Assay Guidelines and Evidence Summariesmentioning
confidence: 99%
“…However, the affinity between human TF and its ligand FVII in the different animal species varies such that the same concentration of TF may have very different effects in the individual species. Evidence from 3 human studies (LOE 6, Good‐Fair), shows that different agonist concentrations produce dissimilar results, arguing for standardization of agonist concentrations . A 1:50,000 dilution of rhTF has been validated and used in one ROTEM and multiple TEG publications in small animals .…”
Section: Databases and Search Terms Usedmentioning
confidence: 99%